The influence of competence, work environment and organizational culture on nurse performance at Dr Soekardjo Tasikmalaya hospital - Peni Cahyati; Dudi Hartono; Siska Evi Martina; Anah Sasmita (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to obtain empirical evidence regarding the effect of competence, work environment, and organizational culture on the performance of nurses in RSUD dr Soekardjo Tasikmalaya. The results of this study can be used as a contribution of thoughts for the leadership of RSUD Dr. Soekardjo Tasikmalaya to improve the performance of nurses through increasing competence and work environment as well as organizational culture.The research method used is descriptive analysis and verification. The data collection used interviews using a questionnaire accompanied by observation and library techniques. Sampling using a simple random sample. Data collection in the field will be carried out in 2022 2. The data analysis technique used Path Analysis.The results showed that competence, work environment, and organizational culture are included in the excellent category, and the performance of nurses, in general, is good. There is an influence of competence, work environment, and corporate culture on the performance of nurses in RSUD Dr. Soekardjo Tasikmalaya. Meanwhile, competence is partially more dominant in influencing the performance of nurses' performance than the work environment and organizational culture